The potential role of differentially expressed tRNA-derived fragments in high glucose-induced podocytes - Zhenxing Zhang; Yunyang Qiao; Jialing Ji; Chan Huang; Huimin Shi; Weihua Gan; Aiqing Zhang (Renal Failure)
The prevalence of diabetic kidney disease (DKD) is increasing annually. Damage to and loss of podocytes occur early in DKD. tRNA-derived fragments (tRFs), originating from tRNA precursors or mature tRNAs, are associated with various illnesses. In this study, tRFs were identified, and their roles in podocyte injury induced by high-glucose (HG) treatment were explored. High-throughput sequencing of podocytes treated with HG was performed to identify differentially expressed tRFs. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed. The expression levels of nephrin, podocin, and desmin were measured in podocytes after overexpression of tRF-1:24-Glu-CTC-1-M2 (tRF-1:24) and concomitant HG treatment. A total of 647 tRFs were identified, and 89 differentially expressed tRFs (|log2FC| ≥ 0.585; p ≤ .05) were identified in the HG group, of which 53 tRFs were downregulated and 36 tRFs were upregulated. The 10 tRFs with the highest differential expression were detected by real-time quantitative polymerase chain reaction (RT-qPCR), and these results were consistent with the sequencing results. GO analysis revealed that the biological process, cellular component, and molecular function terms in which the tRFs were the most enriched were cellular processes, cellular anatomical entities, and binding. KEGG pathway analysis revealed that tRFs may be involved in signaling pathways related to growth hormones, phospholipase D, the regulation of stem cell pluripotency, and T-/B-cell receptors. Overexpression of tRF-1:24, one of the most differentially expressed tRFs, attenuated podocyte injury induced by HG. Thus, tRFs might be potential biomarkers for podocyte injury in DKD.